Ledipasvir plus sofosbuvir fixed-dose combination for 6 weeks in patients with acute hepatitis C virus genotype 1 monoinfection (HepNet Acute HCV IV): an open-label, single-arm, phase 2 study - Deterding, Katja; Pathil-Warth, Anita (The lancet. Infectious diseases, 2017)
Background Early treatment of acute hepatitis C virus (HCV) infection with interferon alfa is highly eﬀective, but can be associated with frequent side-eﬀects. We investigated the safety and eﬃcacy of an interferon-free regimen for treatment of acute HCV infection.